Development of a prototype intelligent compress bin / Muhammad Nabil Nazmi Mohd Nadzir - Mohd Nadzir, Muhammad Nabil Nazmi (2023)
Every day, every restaurant will produce garbage. This waste is produced from kitchen, dining room or from customers. However, bins are not able to accommodate excessive amounts of garbage at one time. So, it needs to be changed and disposed of all the time. So, the objective of this project is to reduce the time rate for changing and disposed garbage with compress the garbage. It’s because the bin will overload with garbage that has a large size. So, if we compress that garbage, it will save a time for bin full of trash and save a plastic bag. However, it’s also kept hygiene because it’s not used our hand to compress that garbage. That garbage was using our leg to press the button to start compress system. That bin will be useful to all restaurant, café and canteen